Playboy Story (Playboy-Taschenbuc, 1980)
Große Autoren sind in diesem Band mit ihren besten Geschichten vertreten: Rudolf Braunburg, Henry Slesar, John Updike, Isaac Bashevis Singer, Tom Griffin, Hal Bennett, John McDonald, Robert McNear, Harlan Ellison, Jerry Sohl